Necessity of oral health intervention in schizophrenic patients – A review (Nepal Journal of Epidemiology, 2017)
Individuals with mental illness often cannot perform day to day activities due to a psychiatric or emotional disorder. Schizophrenia is one such psychiatric disorder characterized by worsening self-care ability with progressing mental illness. This disease may potentially deteriorate oral health by affecting the subject's ability to perform oral hygiene measures. Literature on oral disease manifestations in schizophrenia is limited. Lack of desire for oral health care as well as generally poor awareness of oral health issues in these patients, compounded further by side effects of medications, may complicate dental management in schizophrenic patients. The present review explores clinical features and possible factors associated with oral health status among those with Schizophrenia.